2017
DOI: 10.1007/s11901-017-0349-7
|View full text |Cite
|
Sign up to set email alerts
|

Should AFP (or Any Biomarkers) Be Used for HCC Surveillance?

Abstract: a) Purpose of review To address the controversy around the use of biomarkers for hepatocellular carcinoma (HCC) surveillance in individuals with cirrhosis or chronic hepatitis B who are at risk for development of liver cancer. b) Recent findings Recent studies suggest that surveillance for hepatocellular carcinoma is beneficial, even after adjustment for lead time and other biases. Alpha fetoprotein (AFP) is complementary to ultrasound (US) in surveillance, particularly in obese patients and patients with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 91 publications
2
24
0
Order By: Relevance
“…Although serum AFP levels are routinely used in the clinical setting to monitor the disease status of patients with HCC, the serum AFP levels are found in the normal range for up to 42% of patients with HCC [25]. The use of serum AFP levels for HCC surveillance is not recommended by the American Association for the Study of Liver Diseases due to the lack of specificity [26]. Image examinations such as CT or MRI are still the standards for monitoring the treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Although serum AFP levels are routinely used in the clinical setting to monitor the disease status of patients with HCC, the serum AFP levels are found in the normal range for up to 42% of patients with HCC [25]. The use of serum AFP levels for HCC surveillance is not recommended by the American Association for the Study of Liver Diseases due to the lack of specificity [26]. Image examinations such as CT or MRI are still the standards for monitoring the treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Additional serum alpha-fetoprotein (AFP) analysis should be considered [29]. Particularly an increasing value over time warrants further investigation [30].…”
Section: Hcc Surveillance (Tumour Monitoring) In Patients With Chronimentioning
confidence: 99%
“…However, de novo HCCs occur in 2%‐8% despite SVR, especially in male cirrhotic patients . To date, alpha‐fetoprotein (AFP), a serum glycoprotein, is the only widely used diagnostic biomarker in HCC surveillance . Nonetheless, Farinati et al observed an unsatisfactory sensitivity of AFP, especially in the detection of early‐stage HCC; almost 50% of HCC patients were AFP‐negative (AFP level below 20 ng/mL).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 To date, alpha-fetoprotein (AFP), a serum glycoprotein, is the only widely used diagnostic biomarker in HCC surveillance. 11 Nonetheless, Farinati et al observed an unsatisfactory sensitivity of AFP, especially in the detection of early-stage HCC 12 ; almost 50% of HCC patients were AFP-negative (AFP level below 20 ng/mL). Therefore, to ameliorate early HCC detection and improve efficacy of screening strategies new HCC biomarkers are required.…”
Section: Introductionmentioning
confidence: 99%